THE REFLECTION OF GLOBAL COMPETITON ON TURKISH BANKING SYSTEM: FOREIGN CAPITAL BANKS AND TURKISH BANKING SECTOR (Third Sector Social Economic Review, 2016)
Banks have been the institutions affected the most by revolutions in the last century. Competition is one of the indispensable factors in order to survive for the banks providing new products and services along with the classical banking functions. So, with developments in the financial sector having increased at the global level, international banking activities have increased and domestic banks have been forced to compete with international capital as well as national capital. Some of the people criticize the foreign capital banks about their portions in national banking sector ,but others think that foreign capital banks increase the rivalry and they contribute to the economy of the country. Our study aims to investigate the development process of foreign capital banks in Turkey. So in this context, international banking activities and its evolution, positive and negative effects of foreign capital bankson national banking sectors, foreign capital banks before the period of Republic of Turkey and after the Republic period (especially after 1980’s) are studied in article. However, in previous crisis periods, foreign capital banks moved out from the sector in general. So,the foreign capital banks attitudes during 2008 global economic crisis is another reason for this study. There is a comparison between deposit, loan etc. numbers in the foreign capital banks and other capital groups. Despite the criticism that foreign banks have a big amount of Turkish banking sector, foreign capital banks (they) hold around 15 percent in Turkish banking sector. Unlike 2001 crisis, they didn’t leave the sector in the period of 2008. However, the presence of an effective regulatory and supervisory mechanisms in the Turkish banking sector is an important assurance point that prevents the activities of foreing capital banks that may have adverse effects on the the country or the sector itself.
Keywords: Foreign Capital Banks; Turkish Banking Sector; Competition